1993
DOI: 10.1017/s0272263100011980
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Strategies and SLA in Early French Immersion

Abstract: Examining the role of instruction in second language acquisition (SLA) entails not only a specification of what aspects of SLA stand to be affected but also a clear conception of what is meant by instruction. In this paper the potential of various instructional strategies for promoting SLA among child second language (L2) learners is considered in relation to empirical findings in early French immersion programs. Several principles are proposed concerning the what, when, and how of code-focused L2 instruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
10

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 28 publications
2
82
0
10
Order By: Relevance
“…However, the second category refers to the structures which do not easily let the formulation of clear-cut rules in how to use them, like English prepositions or article system. Furthermore, as Harley (1993) claims English simple past tense is an appropriate form in FonF instruction, as it is different in non-obvious ways from the learners' first language and as it is probably misinterpreted by learners. In addition, …”
Section: Target Structurementioning
confidence: 99%
“…However, the second category refers to the structures which do not easily let the formulation of clear-cut rules in how to use them, like English prepositions or article system. Furthermore, as Harley (1993) claims English simple past tense is an appropriate form in FonF instruction, as it is different in non-obvious ways from the learners' first language and as it is probably misinterpreted by learners. In addition, …”
Section: Target Structurementioning
confidence: 99%
“…Research has consistently shown that proficiency in a language is not developed one linguistic item at a time (Long, 1991). Further, because it is unknown which forms are open to FFI and which are not (Harley, 1993), sequential instruction based on linguistic forms contradicts the findings of research done in both CLT and FFI. It is, therefore, illogical to structure textbooks in such a manner.…”
Section: Issues In Grammar Textbooksmentioning
confidence: 91%
“…Krashen claims that aptitude is irrelevant to language acquisition, because unconscious and implicit, rather than conscious and explicit, processes are at work in natural language development. Abrahamsson and Hyltenstam (2008), however, refer to more recent studies by Harley andHart (2002), DeKeyser (2000) which have suggested that Stellenbosch University http://scholar.sun.ac.za language aptitude may play a decisive role in naturalistic SLA -and perhaps an even more decisive role than it plays in instructed SLA -because acquiring a language implicitly, by having to discover grammatical regularities and phonetic patterns merely from language exposure, can be seen as an even greater challenge than learning it through pronunciation tutoring and explicit grammar instruction (Abrahamsson & Hyltenstam 2008: 486). Abrahamsson and Hyltenstam's (2008: 503) own research results have revealed that "language aptitude is not a necessary condition for eventually sounding like a native speaker, but it is a significantly advantageous condition for attaining a level of L2 proficiency identical to that of native speakers".…”
Section: 72mentioning
confidence: 99%